Azimuthal reorientation of adsorbed molecules induced by lateral interactions: benzene/Ni(110) - Huber, W.; Weinelt, M.; Zebisch, P.; Steinrück, Hans-Peter (Surface Science, 1991)
The adsorption of benzene on the Ni(110) surface was studied by TPD, LEED, NEXAFS and ARUPS. At initial coverages below θ = 0.10 ML (relative to Ni) benzene completely decomposes upon heating. At higher coverages molecular benzene desorption is also observed. At the saturation coverage of 0.23 ± 0.04 ML a sharp c(4 × 2) LEED pattern is observed with weak additional reflexes indicating a larger unit mesh. The ARUPS measurements for a dilute layer (θ ≃ 0.5θ ) suggest an orientation of the molecular plane parallel to the surface with C symmetry of the adsorption complex benzene/Ni(110) and the molecules azimuthally oriented with their corners along [001]. For the saturated layer the molecular plane is still parallel to the surface but the symmetry of the adsorption complex is lowered to C , due to an azimuthal rotation of the benzene molecules induced by strong lateral interactions in the densely packed saturated layer. The 2alg band shows strong dispersion (0.8 eV) with the periodicity of the 2D bandstructure corresponding to a c(4 × 2) structure. For the coadsorption of benzene + CO a sharp c(4 × 4) LEED structure is observed with identical CO and benzene coverages of 0.12 ML. The electronic structure, orientation and symmetry of benzene in the coadsorbed layer is identical to that in the dilute pure layer. The photon energy dependence of the photoionization cross section of the 2elu level of benzene in the saturated layer shows a maximum at a photon energy of 25 eV, similar to benzene on Ni(111); the corresponding electron emission is centered along the surface normal. The NEXAFS spectra for the dilute and the saturated layer at normal incidence are also indicative of a flat-lying benzene molecule. © 1991.